Histomorphological scoring of murine colitis models: A practical guide for the evaluation of colitis and colitis-associated cancer - Marianne Remke; Tanja Groll; Thomas Metzler; Elisabeth Urbauer; Janine Kövilein; Theresa Schnalzger; Jürgen Ruland; Dirk Haller; Katja Steiger (Experimental and Molecular Pathology)
Background and aims: Histomorphology is a powerful and cost-efficient tool for evaluating inflammatory and neoplastic conditions. Inflammatory bowel disease (IBD) is a widespread condition with globally rising incidences, and a lot of research is done to better understand the pathogenesis of IBD and to identify potential therapeutic approaches. However, standardized and reproducible scores for the histomorphological evaluation of murine IBD models are lacking. Therefore, we aimed to develop an easy-to-use and reproducible score for standardized assessment of colitis and associated cancer models. Methods: In this study, samples from three different colitis models with and without associated cancer formation were analyzed to develop a universal, robust, and reproducible score for the grading of murine colitis models using the following three parameters: 1. Extent of leucocyte infiltration, 2. Tissue damage, 3. Architectural disruption of the mucosa. Results: A scoring system was established for different kinds of colitis models (genetically induced enterocolitis, genetically induced metabolic injury, and chemically induced colitis-associated cancer) and all stages of the disease, from mild inflammatory changes to severe inflammation with neoplastic changes as the extreme extent of IBD. The scoring scheme is easy to use, can easily be learned, and proves to have a high interrater reliability. Conclusions: We propose a robust histological scoring system for the assessment of murine colitis and colitis-associated cancer models, giving more researchers access to conclusive and reliable histological assessment.